Development and Characterization of Rice Husk and Recycled Polypropylene Composite Filaments for 3D Printing (2021)
Nowadays the use of natural fiber composites has gained significant interest due to their low density, high availability, and low cost. The present study explores the development of sustainable 3D printing filaments based on rice husk (RH), an agricultural residue, and recycled polypropylene (rPP) and the influence of fiber weight ratio on physical, thermal, mechanical, and morphological properties of 3D printing parts. Thermogravimetric analysis revealed that the composite’s degradation process started earlier than for the neat rPP due to the lignocellulosic fiber components. Mechanical tests showed that tensile strength increased when using a raster angle of 0◦ than specimens printed at 90◦ , due to the weaker inter-layer bonding compared to in-layer. Furthermore, inter layer bonding tensile strength was similar for all tested materials. Scanning electron microscope (SEM) images revealed the limited interaction between the untreated fiber and matrix, which led to reduced tensile properties. However, during the printing process, composites presented lower warping than printed neat rPP. Thus, 3D printable ecofriendly natural fiber composite filaments with low density and low cost can be developed and used for 3D printing applications, contributing to reduce the impact of plastic and agricultural waste.